Peripheral nerve stimulation for pudendal neuralgia and other pelvic pain disorders: current advances - Kovacevic, Natalija; Sirls, Larry; Gilleran, Jason; Peters, Kenneth (Frontiers in Urology, 2023)
Chronic pelvic pain conditions such as pudendal neuralgia pose significant treatment difficulty due to their elusive etiology and diverse symptomatology. Initially approved as a third or fourth-line treatment of non-obstructive urinary retention and fecal incontinence, neuromodulation has also proven effective for pelvic pain associated with urinary dysfunction. Recently, sacral and pudendal neuromodulation has demonstrated efficacy in managing a spectrum of chronic pelvic conditions including refractory pudendal neuralgia. The individualized approach of peripheral neuromodulation has opened new avenues for tailored medical interventions, extending its application to conditions such as pudendal neuralgia, post sling pain, and vulvodynia. New technologies leading to miniaturized neuromodulation devices such as Freedom® stimulators (Curonix), allows us to implant leads and modulate nerves at precise pain targets. Further experience and research is needed to assess the impact of targeted neuromodulation on managing complex pelvic pain conditions.